If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -1y = 5y Solving 24 + -1y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 24 + -1y + -5y = 5y + -5y Combine like terms: -1y + -5y = -6y 24 + -6y = 5y + -5y Combine like terms: 5y + -5y = 0 24 + -6y = 0 Add '-24' to each side of the equation. 24 + -24 + -6y = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -6y = 0 + -24 -6y = 0 + -24 Combine like terms: 0 + -24 = -24 -6y = -24 Divide each side by '-6'. y = 4 Simplifying y = 4
| 4(a+3)=11 | | 0.21y-0.8=0.11y+1-0.8y | | t(t+5)=2t^2+7 | | (x+7)(x+7)=2x^2+13x+19 | | 5m-26=-25+6m | | 5x^2-40x^2+75x= | | 3(5x+1)+6(5x+1)=2 | | .8m-.2m=9 | | 2x^4-3x^3+2x^2-15x+14=0 | | u^2-6u+8=0 | | -32xy^5+40x^3y^5-16xy^5= | | 8y=7y-45 | | 3t^3-9t+6=0 | | 27c^4-125c=0 | | 9x^2-5x=3 | | -8=-x-4 | | 3x=2-4y | | 10y=5y-5 | | 4(3x+4)=52 | | 35x^2-16x-3=0 | | 4x+3=-45 | | 9x+14=-67 | | w^2+4w-x^2+4=0 | | -7y+5(y-4)=-18 | | 6x+13=-5 | | 2x-0.35=.20 | | 4x+6=-62 | | 7(4x+1)=3(12x-3) | | 92x+31=72 | | -3x+9=30-6x | | 2c/10=24 | | (5c+6)(5c-6)=0 |